The child soldiers of Africa's Red Army - Berger, Carol, 1959- author.
1 online resource
Keywords: "This book examines the role of social process and routinised violence in the use of underaged soldiers in the country now known as South Sudan during the twenty-two-year civil war between Sudan's northern and southern regions. Drawing on accounts of South Sudanese who as children and teenagers were part of the Red Army-the youth wing of the Sudan People's Liberation Army (SPLA)- the book sheds light on the organised nature of the exploitation of children and youth by senior adult figures within the movement. The book also includes interviews with several of the original Red Army commanders, all of whom went on to hold senior positions within the military and government of South Sudan. The author chronicles the cultural transformation experienced by members of the Red Army and considers whether an analysis of the processes involved in what was then Africa's longest civil war can aid our understanding of South Sudan's more recent descent into ethnicised conflict. As such, it will appeal to scholars of sociology, anthropology and political science with interests in ethnography, conflict and the military exploitation of children"--